The - Bhidé, Amar V. (Oxford University Press, 2000)
In a field dominated by anecdote and folklore, this landmark study integrates more than ten years of intensive research and modern theories of business and economics. The result is a comprehensive framework for understanding entrepreneurship that provides new and penetrating insights. Examining hundreds of successful ventures, the author finds that the typical business has humble, improvised origins. Well-planned start-ups, backed by substantial venture capital, are exceptional. Entrepreneurs like Bill Gates and Sam Walton initially pursue small, uncertain opportunities, without much capital, market research, or breakthrough technologies. Coping with ambiguity and surprises, face-to-face selling, and making do with second-tier employees is more important than foresight, deal-making, or recruiting top-notch teams